THE EFFECTIVENESS OF USING GROUP DISCUSSION ON STUDENTS’ SPEAKING SKILL: AN EXPERIMENTAL STUDY AT - Baiq Syarla Viergina Deanova; Nawawi; Rizki Kurniawan Hoesnie (Journal of English Education Forum (JEEF), 2023)
The title of this thesis is "Assessing the Efficacy of Utilizing Group Discussion to Enhance Students' Speaking Skill." The study was conducted among second-grade students at SMPN 1 Masbagik and falls under the category of Experimental Research. The data collection process involved a pre-test, treatment, and post-test. The target population consisted of second-grade students at SMPN 1 Masbagik, all of whom exhibited a similar proficiency level in speaking skills. To determine the sample, a purposive random sampling technique was employed. The sample comprised two groups: the experimental group (XD) and the control group (XC). The Inquiry Technique was used to teach the experimental group, while the control group received instruction through the Grammar Translation Method. Each group consisted of 30 students. Notably, the experimental group demonstrated a higher post-test score compared to the pre-test score. Specifically, 15 students scored higher than the mean score of 38.7 in the pre-test. Following treatment involving the utilization of the Group Discussion technique, the experimental group exhibited improved performance, with 28 students achieving scores higher than the mean score in the post-test (46.73). Subsequently, the data was subjected to t-test calculations, yielding a value of 3.19. This t-test value exceeded the critical t-values at the 0.05 confidence level (2.021) and the 0.01 confidence level (2.704) with a degree of freedom of 58. Consequently, the null hypothesis stating that the "Group Discussion technique does not increase students' speaking skill" was rejected, while the alternate hypothesis proposing that the "Group Discussion technique increases students' speaking skill" was accepted.